2020
DOI: 10.1021/acssensors.0c01879
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multiple Beams on Plan Quality, Linear Energy Transfer Distribution, and Plan Robustness of Intensity Modulated Proton Therapy for Lung Cancer

Abstract: The increase of proton beam number might provide higher degrees of freedom in the optimization of intensity-modulated proton therapy planning. In this study, we aimed to quantitatively explore the potential benefits of the increased beam number, including dose volume histogram (DVH), linear energy transfer volume histogram, and DVH bandwidth metrics. Twelve patients with lung cancer are retrospectively selected. Four plans were created based on internal target volume (ITV) robust optimization for each patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 37 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…17,22,23 and from 3.1 to 3.2 keV/µm for the lung. 24 For the CTV in our study, the +3.5% and -3.5% range uncertainty scenarios without the setup uncertainties showed a systematic increase and decrease in the LET d , respectively. For the CTV, the variations in the mean LET d were found to be ≤ 0.5 keV/µm, with an average value of 0.4 keV/µm.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…17,22,23 and from 3.1 to 3.2 keV/µm for the lung. 24 For the CTV in our study, the +3.5% and -3.5% range uncertainty scenarios without the setup uncertainties showed a systematic increase and decrease in the LET d , respectively. For the CTV, the variations in the mean LET d were found to be ≤ 0.5 keV/µm, with an average value of 0.4 keV/µm.…”
Section: Discussionmentioning
confidence: 48%
“…In the current study, we noticed that the mean LET d of the total lung in nominal plans ranged from 2.4 to 4.0 keV/µm, which was slightly higher than the mean LET d (0.8─1.8 keV/µm.) of lung reported by Shang et al 24 for a three-beam arrangement technique. Hahn et al 15 found the OARs of brain cancer patients being the most sensitive to range uncertainties when compared to prostate and head and neck cancer.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Increasing the number of beams can reduce the impact of each of these uncertainties, and studies have shown that increasing the number of beams in a plan can improve robustness. 11,12 Combining these planning techniques; treating with multiple beams, using robust optimization, and optimizing and calculating with MC, can clearly be beneficial for the patient. However, it can be challenging and time consuming for the planning team.…”
Section: Introductionmentioning
confidence: 99%